2018
DOI: 10.3389/fevo.2018.00192
|View full text |Cite
|
Sign up to set email alerts
|

Predatory Mites (Acari: Phytoseiidae) in Agro-Ecosystems and Conservation Biological Control: A Review and Explorative Approach for Forecasting Plant-Predatory Mite Interactions and Mite Dispersal

Abstract: Phytoseiidae mites are efficient predators, able to control pest mites and small arthropods in crops all over the world, using three biological control strategies: (i) augmentation, (ii) classical, and (iii) conservation. This paper focuses on the latter strategy. Most of those predatory mite species are generalist predators; they are naturally present in agro-ecosystems both on crops and adjacent natural vegetation. Because of such characteristics, their occurrence is usually associated with the use of fewer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 103 publications
(140 reference statements)
3
24
0
Order By: Relevance
“…Off-field habitats represent a reservoir for phytoseiid populations that can potentially colonize crops [62,63]; thus compatibility between pesticides and phytoseiids could be promoted by reducing pesticide drift. Low-drift nozzles and anti-drift adjuvants were effective in controlling key pests in orchards and vineyards, while they did not affect phytoseiids [64].…”
Section: Ecological Selectivity and Management Practices That Enhance Compatibilitymentioning
confidence: 99%
“…Off-field habitats represent a reservoir for phytoseiid populations that can potentially colonize crops [62,63]; thus compatibility between pesticides and phytoseiids could be promoted by reducing pesticide drift. Low-drift nozzles and anti-drift adjuvants were effective in controlling key pests in orchards and vineyards, while they did not affect phytoseiids [64].…”
Section: Ecological Selectivity and Management Practices That Enhance Compatibilitymentioning
confidence: 99%
“…Grape varieties strongly differ in leaf surface morphology and thus microhabitat quality for plant-inhabiting mites. Leaf surface morphology is generally acknowledged to be a decisive factor for the occurrence and abundance of plant-inhabiting arthropod, especially mite, populations and pollen deposition [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen of the 16 pairs of integrated and organic vineyards within a predefined radius of investigation had heterogeneous varieties and three had homogeneous varieties (Table S1). There is ample evidence that grape leaves differ in their quality as mite microhabitat among grape varieties [3,4]. For predatory mites, numerous studies have shown that one highly critical factor is the leaf surface morphology, and here, especially the occurrence and density of trichomes, bristles and domatia-like structures on the abaxial side of the leaf [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In European vineyards, phytoseiid mites (Acari) are reported as efficient predators of tetranychid and eriophyoid mites (Acari) and, in absence of prey, can survive by feeding on pollen, fungi, or plant exudates [ 23 , 24 , 25 ]. In the grape growing area of north-eastern Italy, Kampimodromus aberrans (Oudemans) is among the most frequently observed phytoseiid species in vineyards and its persistence is favored by the use of selective pesticides and habitat management strategies [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%